Comparative Analysis Reveals Concentration-Dependent And Site-Specific Detoxification Gene Expression Patterns In Pyrethroid Resistant Anopheles Gambiae S.L. From Accra, Ghana - Owusu-Asenso, C.M.; Abdulai, A.; Sraku, I.K.; Attah, S.K.; Aboagye-Antwi, F.; Afrane, Y.A. (Scientific Reports, 2026)
The role of detoxification enzymes in pyrethroid resistance intensity among malaria vectors remains a critical area of research. This study evaluated the role of detoxifying enzymes in driving resistance intensity in Anopheles mosquitoes from high insecticide resistance sites in Accra, Ghana. Larvae were collected from Tema, Abossey Okai, and Dansoman, and bioassays were performed on 3–5 days old adult females by exposing them to deltamethrin at discriminating concentrations (1× = 0.05%, 5× = 0.25%, and 10× = 0.5%) to assess resistance intensity. A piperonyl butoxide (PBO) synergist assay was used to test the involvement of cytochrome P450s, while qRT-PCR quantified expression of detoxification genes (CYP6P1, CYP9K1, CYP6M2, CYP6P3, CYP4G16, GSTE2, and CYP6Z1). kdr mutations (L995F, L995S) were genotyped. High-intensity resistance was observed across all sites [deltamethrin 10× MR = 75–91%]. Pre-exposure to PBO significantly increased mortality (Tema: 13–56%; Abossey Okai: 20–91%; Dansoman: 34–88%, P < 0.001), however, complete susceptibility was not restored. The L995F mutation was present at similar frequencies in resistant and susceptible mosquitoes. Transcriptomic profiling revealed concentration-dependent and site-specific expression: Tema; CYP9K1, CYP6M2, CYP6P1, and CYP6P3 were significantly overexpressed (FC = 43.71–1222.98, P < 0.05), while CYP4G16 expression increased with insecticide concentration. In Abossey Okai, CYP9K1, CYP6P1, CYP6M2, and CYP6P3 were overexpressed (FC = 5.54–162.84). Mosquitoes from Dansoman showed generally low expression, however, CYP6M2 and CYP6P3 were overexpressed (FC = 120.80–292.68). These findings may suggest the dominant role of metabolic resistance, particularly P450-mediated detoxification in driving high pyrethroid resistance intensity in Ghana.
Research Article
Keywords: Pyrethroid resistance intensity; Metabolic gene expression; Concentration-dependent gene expression; Site-specific gene expression; Anopheles Gambiae s.l.; Kdr mutations